Upaya Pencegahan dan Penurunan Stunting di Kelurahan Cibuluh, Kota Bogor melalui Program “Cinta Itu Penting” - Salsabillah, Asyfa Thalita; Waliudin, Muhammad Sulthan; Khairunnisa, Salis; Maharani, Aulia Cinta; Setiyawan, Hazfi; Ridho, Ahmad Yusuf; Aulia, Nazuwa; Romauli, Eztheriyhana Judika; Muharomah, Nurul Ismah; Rahma, Anisa (Jurnal Pusat Inovasi Masyarakat, 2025)
Stunting and malnutrition are problems that affect the development and growth of toddlers due to a lack of nutrition and nutrient intake during early growth, especially in the first two years of life. Cinta Itu Penting (Cibuluh Tuntaskan Ikhtiar untuk Penanganan Stunting) program aims to help prevent and reduce the incidence of stunting in Cibuluh Village by increasing community understanding of the importance of nutritional intake. This activity involves assistance in determining stunting and nutrition status based on anthropometric measurements, as well as socialization to Integrated Service Post (Posyandu) participants. In this activity, a pocket book was also made. In addition, there was also socialization about stunting to pregnant women and the provision of healthy food. The target number of participants in the implementation of Cinta Itu Penting was 30 people. Based on the results of the pre-test and post-test, it is known that there is an increase in the knowledge of pregnant women about the incidence of stunting and how to prevent it. In addition, the results of this KKNT activity have also produced a book which can then be utilized by posyandu to educate pregnant women